2019
DOI: 10.1111/padm.12577
|View full text |Cite
|
Sign up to set email alerts
|

Understanding relationships between public service motivation and involvement in socio‐political organizations: Perspectives of organizational field theory

Abstract: The study provides insights about public service motivation values and participation in socio‐political organizations. It applies organizational field theory to a sample of similar public and nonprofit service providers in a border region of two independent states. The results reveal that socio‐political activities bear different meanings for individuals from different sectors and countries. Thus, from an institutional perspective, despite offering similar services, the organizations studied belong to differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 58 publications
(152 reference statements)
1
8
0
Order By: Relevance
“…The negative relationship between COM and the user's reporting rate may even indicate that an engagement with the platform is viewed as something negative that keeps individuals with high levels of COM from engaging in activities typically associated with COM, such as personally helping people in need. This argument is indirectly supported by recent research by Prysmakova's (2019), who found that party membership, which also presents a prosocial type of behavior that is not directed at personally helping people in need, correlates negatively with the PSM dimension "compassion".…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The negative relationship between COM and the user's reporting rate may even indicate that an engagement with the platform is viewed as something negative that keeps individuals with high levels of COM from engaging in activities typically associated with COM, such as personally helping people in need. This argument is indirectly supported by recent research by Prysmakova's (2019), who found that party membership, which also presents a prosocial type of behavior that is not directed at personally helping people in need, correlates negatively with the PSM dimension "compassion".…”
Section: Discussionmentioning
confidence: 74%
“…A final contribution of this study is the insight regarding the role of PSM among citizens, since most previous research on PSM has focused on public servants (Ritz, Brewer, and Neumann 2016) or used data from student samples (e.g., Christensen and Wright 2018;Holt 2019;Stritch and Christensen 2016b). Public servants' PSM has, for instance, been found to be associated with prosocial types of behavior, such as donating blood and volunteering (e.g., Houston 2006;Prysmakova 2019;Schott et al 2019;Ritz et al 2020). Positive examples of studies that do investigate the role of PSM among citizens are and Pedersen, Stritch, and Taggart (2017).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the administration, either through the means of legislature or through the means of promoted norms and standards, might put some limitations on employees' participation in some social activities, like political campaigns or union strikes, or require mandatory volunteering at job sites. The PSM level of public sector employees reflects these restrictions correspondingly (Prysmakova, 2019). Institutional, legal, and political traditions define the ways in which products and services are exchanged on economic markets (Bullock et al, 2015).…”
Section: National Level: Public Sectormentioning
confidence: 99%
“…Other studies mention values in passing, for example, collectivist values in Taiwan (Cheng, 2019), Turkey (Battaglio & Gelgec, 2017), and Vietnam (Tuan, 2018b), religious values in Bhutan (Tshiteem & Everest-Philips, 2016), and the role of ideology in Belarus and Poland (Prysmakova, 2019). Clearly, the importance of context in how employees perceive their work and the drivers behind their behaviours is recognised.…”
Section: The Importance Of Context and Further Improvement Of Measurementioning
confidence: 99%